Leishmaniose Visceral: fatores determinantes e condicionantes de uma epidemia anunciada em Araguaína-TO - Silva, Marivaldo Cavalcante da (2013)
The main objective of this study is to understand the main responsible factors for the spread of the epidemic of VL in Araguaína / TO. The survey was conducted from an extensive literature review, photographic records, use of satellite images, interviews and questionnaires with the population, agents to combat endemic diseases, reporter on televised media as well as through information and data available on the Internet as a database DATASUS. The main source of information about the number of cases and their distribution in Araguaína were provided by the Leishmaniasis Management Center in Palmas. The triple burden of diseases that the city has faced, combined to poor conditions of the population lifestyle are factors that contribute to spread the VL epidemic. The lack of urban infrastructure, the accumulation of garbage and household conditions, the high rate of animals like dogs, chickens and horses without the due health care can be contributing to the epidemic situation at the present. The mode of life and habits of the most population, the sprawl of the city that has advanced among the natural habitat of the mosquito that transmits the LV is another factor that contributes to the current state of the epidemic. One of the measures to minimize the situation was implanted the distribution of pet collars impregnated with insecticide repellents, however, the areas with the highest rates were not included, demonstrating the lack of discretion about the distribution of collars. It is necessary to carry out some joint activities with various municipal departments, approaching together to the population and searching the due health care, improving their quality of life.